Auspicious Symbols of Chinese Ceramics found from Archaeological Excavation in Northern Thailand - Meepukdee, Khomsi (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2024)
Chinese ceramics are important as archeological evidence. Normally, they have been found together with Lanna ceramics and ceramics from other countries. This article aims to study the patterns and symbols of Chinese ceramics found in northern Thailand from archeological excavation in the past century. It is found that the decorative patterns and symbols can be classified into seven groups. Auspicious symbols such as flaming pearls are often shown with the dragon, lingzhi (sacred fungus), or key fret. Chinese characters are normally shown at the bottom of ceramics or Chinese characters found in the king’s seal. Nobility is found as a person symbol. Animal symbols include cranes, dragons, Qilin, horses galloping in the waves, and cats. Natural symbols include clouds and waves. Floral and botanical symbols include lotus, chrysanthemum, artemisia leaves, and floral scroll designs. Besides, special decorative symbols include Ju-I patterns, arabesque designs, and double Vajra tied with ribbons. The patterns and symbols of Chinese ceramics have influenced Lanna ceramics which then developed into unique designs.